1996
DOI: 10.1021/jf950525o
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Volatiles Derived from Citrobacter freundii Fermentation of a Trypticase Soy Broth

Abstract: Twenty-two compounds emanated as volatiles from an 8-day fermentation of trypticase soy broth by Citrobacter freundii, American Type Culture Collection (ATCC 8090), were identified by dynamic headspace analysis techniques. Compound identifications were made on the basis of a comparison of Kovats indices and GC/MS spectra for unknowns and authentic samples. Of the compounds identified, nine were pyrazines, four were alcohols, two were aldehydes, two were ketones, two were esters, two were sulfides, and one was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 18 publications
4
24
0
1
Order By: Relevance
“…Lee et al (1995) analysed the volatile components of the Klebsiella pneumoniae bacterial fermentation of a trypticase soy broth that was attractive to A. ludens and identified a total of 21 compounds including alcohols, pyrazines, ketones, acids and phenols, the most abundant being 3-methyl-1-butanol, 2-phenylethanol, 2,5-dimethylpyrazine, 2-methyl-1-propanol and 3-(methylthio)-1-propanol. In the same way, DeMilo et al (1996) identified 22 volatile compounds derived from Citrobacter freundii fermentation of a trypticase soy broth. The most abundant volatiles were 3-methyl-1-butanol, phenol, 2,5-dimethylpyrazine, 2-phenylethanol and 2-methyl-1-propanol and were shown to attract A. ludens.…”
Section: Dipteramentioning
confidence: 95%
“…Lee et al (1995) analysed the volatile components of the Klebsiella pneumoniae bacterial fermentation of a trypticase soy broth that was attractive to A. ludens and identified a total of 21 compounds including alcohols, pyrazines, ketones, acids and phenols, the most abundant being 3-methyl-1-butanol, 2-phenylethanol, 2,5-dimethylpyrazine, 2-methyl-1-propanol and 3-(methylthio)-1-propanol. In the same way, DeMilo et al (1996) identified 22 volatile compounds derived from Citrobacter freundii fermentation of a trypticase soy broth. The most abundant volatiles were 3-methyl-1-butanol, phenol, 2,5-dimethylpyrazine, 2-phenylethanol and 2-methyl-1-propanol and were shown to attract A. ludens.…”
Section: Dipteramentioning
confidence: 95%
“…Headspace volatiles produced by each bacterium were collected using a setup described by DeMilo, Lee, Moreno and Martinez (1996) with slight modifications. Bacteria were grown in either 100 ml of tryptic soy broth (TSB) (Difco Laboratories, Detroit, MI, USA) or M9 minimal medium (per litre: 16 g NaHPO 4 -7H 2 O, 3.75 g KH 2 PO 4 , 0.625 g NaCl, 1.25 g NH 4 Cl, 0.24 g 1M MgSO 4 , 0.01 g 1M CaCl 2, and 20 ml of 20% glucose as the carbon source).…”
Section: Collection and Analysis Of Volatile Organic Compoundsmentioning
confidence: 99%
“…In particular, methyl ketones with an odd number of carbon atoms were reported to derive from the decarboxylation of even-numbered β-keto acids. The production of methyl ketones bearing an even number of atoms rarely occurs, since they derive from odd numbered fatty acids; however, production of 2-butanone has also been reported as a component of VOC emissions from several bacteria (DeMilo et al 1996;Dickschat, Martens, et al 2005;Elgaali et al 2002;Lee et al 1995;Robacker and Bartelt 1997;Sunesson et al 1997). Esters also constitute a very important class of bacterial VOCs, and their enhanced volatility compared to their precursor carboxylic acids facilitates their determination by headspace sampling and gas-chromatographic analysis.…”
Section: Effect Of Eugenol On Voc Profile Of Ecolimentioning
confidence: 99%